Development of State Civil Apparatus at the Department of Culture and Tourism of Tulungagung Regency - Gusti Ayu Ambarawati; Helwani; Filipo Royan Abriera; Ayu Raditya Kencana Dewi (Institut Pemerintahan Dalam Negeri, 2025)
The development of state civil apparatus resources plays a strategic role in improving organizational performance and the quality of public services, particularly in the cultural and tourism sectors. This study aims to analyze the implementation of apparatus development, identify inhibiting factors, and examine the efforts undertaken to enhance the quality of human resources at the Department of Culture and Tourism of Tulungagung Regency. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation. Informants were selected using purposive sampling and snowball sampling techniques. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that apparatus development has been implemented through education, training, and job rotation based on the merit system. However, its implementation has not been optimal, particularly in technical and managerial training programs. The main inhibiting factors include limited budget allocation, low employee motivation, and inadequate facilities for competency development. Efforts to overcome these obstacles include collaboration with third parties and the utilization of webinars to improve apparatus competencies. This study concludes that apparatus development should be conducted in a more planned and sustainable manner, supported by adequate budgetary policies and increased employee motivation, to enhance organizational performance and support regional tourism development.